The Role Of Literacy In Managing Financial Technology - Arifiani, Rahmawaty (Journal of Management, 2024)
The purpose of this study is to examine how financial management practices, through their mediation by financial literacy and financial technology (fintech), affect business performance. This study employs a quantitative research design with Sobel tests for mediation testing and covariance-based partial least squares (PLS) testing techniques. Users of "Halofina" located throughout the Bandung City region were given surveys both offline and online as part of the data collection process. Purposive sampling techniques were used to choose samples from the population, which consisted of all users of the "Go Halofina" application. There were 92 research subjects in total. The following findings are based on research: First, fintech significantly improves the performance of businesses. Second, the performance of businesses is significantly improved by financial literacy. Third, the performance of businesses is significantly improved by financial management practices. Moreover, it is demonstrated by the fourth and fifth assumptions that financial literacy and fintech significantly improve financial management behaviour. Financial management practices are shown to mitigate the impact of fintech and financial literacy on company performance in the sixth and seventh hypothesis.